universitas pamulang Teknik informatika: Aplikasi Arduino Pada Pembuatan Tutup Sunroof Otomatis Dengan Sensor Air Hujan Pada Tanaman Hidroponik Dengan Simulasi Air Hujan - Irawan, Sandy Bayu; Wasis Haryono (JUPIK : Jurnal Penelitian Ilmu komputer, 2025)
Hydroponic plants will have good growth if the pH of the water is between 6-7. However, rainwater that falls can affect the pH of hydroponic plant water. Then an Arduino application was made to make an automatic sunroof cover with a water sensor in a rainwater simulation. By making this application it is intended that the sunroof can open and close automatically which can detect rainwater. This Arduino application generates data that can provide warnings when it rains. The method used is the R&D (Research and Development) method which is a process or steps to develop a product. The expected results with the Arduino application in making automatic sunroof covers with water sensors in rainwater simulations can help hydroponic farmers deal with rainfall. Hydroponic farmers can be assisted in closing the sunroof on hydroponic plants.Keywords: Hydroponics, Microcontroller, Sunroof, Rain Drop Sensor.